Ice massage. Effects on exercise-induced muscle damage - Howatson, G.; van Someren, K. A. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The purpose of this study was to examine the effects of ice massage on the signs and symptoms associated with exercise-induced muscle damage. Methods: Nine recreationally resistance trained males performed an exercise protocol designed to induce muscle damage on 2 separate occasions; this was performed on the dominant or non-dominant arm in a random cross over design. The protocol consisted of 3 sets of 10 repetitions of single arm biceps curls, at 70% of a pre-determined one repetition maximum (1RM), with the eccentric phase of the contraction extended to 7 seconds. Subjects were also randomly assigned to an ice massage group or control group in the cross over design and received treatments immediately post-exercise, 24 hours and 48 hours post-exercise. 1RM, plasma creatine kinase (CK), muscle soreness (DOMS), limb girth and range of motion (ROM) were measured pre, immediately post, 24 hours, 48 hours and 72 hours post-exercise. Results: Significant time effects were observed for all dependent variables (p<0.05), though no significant group effects were observed. A group by time interaction was found for CK (p<0.05), which at 72 hours post-exercise was significantly lower in the ice massage group (p<0.05). Conclusion: These results indicate that although ice massage reduces the appearance of CK it has no other effect on signs and symptoms associated with exercise-induced muscle damage.